ULTIMA RATIO DEORUM - Alexis V. Halapsis (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose of this article is to investigate the role that the "miraculous" – that is, everything that goes beyond “natural” – plays in the worldview of Western man. Methodology. I do not consider “miracles” as the facts of nature, but as the facts of culture, so in this article I am not talking about specific cases of violation of “laws of nature”, but about the place of “miraculous” in the view of the world of Western man and those transformations, that occur with this element outlook influenced the development of information technologies. Novelty. It has been proved that miracles should be sought in mind, because the “miraculous” event does our attitude towards it. Moreover, it is impossible to determine the “true miracle”, while we are “inside” the reality. It has been demonstrated that influenced the development of society is transformed representations of gods and miracles. It has been discovered fundamental shift associated with the transition from mythology-as-faith to mythology-as-show. However, even within the latter remains a need for miracles, though, and goes to a completely different level. Conclusions. The term "miracle" has no meaning outside of accepted socio-cultural settings. The last set as the “natural” conditions and admissibility (inadmissibility) of its violation. And these installations are formed by social institutions, which in this age and at this time have a weight sufficient to impose their views to all the congregation or the greater part. Any extraordinary event can be explained by the action of internal agents unknown to us, and their ability to alter the reality is not necessarily superior to even our own capabilities. The only thing we can not do – is to change the source code of being (e.g., fundamental physical constants). This could make only creatures that are not spelled out in these source codes. However, people have not seen anything like it, and scarcely become witnesses of such events.